PENERAPAN METODE PEMBELAJARAN BIOLOGI DI LUAR KELAS UNTUK MENINGKATKAN MINAT BELAJAR MAHASISWA - Riska Septia Wahyuningtyas (Universitas Tribhuwana Tunggadewi, 2023)
This study aims to determine whether the application of learning methods outside the classroom can increase student interest in learning. This study used a classroom action research method involving 18 S1 students of Biology Education FKIP UKI. The steps of this research include the planning stage, action, action implementation, observation stage, and reflection stage. The results showed that from the pretest results of student learning interest, an average score of 69.6429 was obtained. This score shows a very low average learning interest score before applying learning methods outside the classroom. The results of this study showed that the score of interest in learning after learning methods outside the classroom increased from the pretest results of 69.6429 to the results of cycle 1, which was 78.9163, then the results of cycle 2 to 82.3153. The difference in scores has been analyzed using SPSS with the T test and shows a significant result of 0.01. This shows that the application of learning methods outside the classroom can increase student interest in learning.